Answer:
See explanations below
Step-by-step explanation:
Given the functions f(x)=2x+3 and g(x)=x^2-1
a. Find f(g(x))
f(g(x)) = f(x^2-1)
f(g(x)) = 2(x^2-1)+3
f(g(x))= 2x^2-2+3
f(g(x)) = 2x^2+1
Hence the composite function f(g(x)) is 2x^2+1
b) g(f(x)) = g(2x+3)
g(f(x) = (2x+3)^2-1
g(f(x)) = 4x^2+12x+9-1
g(f(x)) = 4x^2+12x+8
We need more information or a picture please :)
Answer:
B
Step-by-step explanation:
The red graph is a horizontal translation of 5 units left followed by a reflection in the x- axis.
Given f(x) then f(x + a) is a horizontal translation of f(x)
• If a > 0 then a shift to the left of a units
• If a < 0 then a shift to the right of a units
The black graph is shifted 5 units left, thus
f(x) → f(x + 5)
Under a reflection in the x- axis
a point (x, y ) → (x, - y )
Note that the y- coordinate of the image is the negative of the original
Note also that
= - y, thus
= f(x + 5) → B
You didn't ask a question but its called a period